BESS as a UPS to Power Systems With High Solar Penetration - Aluthge, C. Devin; Hemapala, K. T. M. Udayanga; Lucas, J. Rohan (Frontiers in Energy Research, 2021)
This paper analyses the need of primary and secondary frequency control for a low inertia power system. The Sri Lankan Power System is taken as a case study. Due to the high penetration of wind and solar injection to the Sri Lankan power system, the inertia of the system has been reduced drastically. Simulations have been carried out on a single feeder as it is impracticable to install a large battery energy storage system (BESS). The problems of dynamic stability of the current system due to high solar power penetration, is analyzed. The repercussions of these problems to the power system are then discussed related to the stability of the system where there is severe machine tripping. Remedial action needed to be taken to increase the power quality of the power system, namely BESS and supercapacitors is presented. A comparison of the inertia of the current system and the system when conventional power replaces solar power is also analyzed. The paper addresses on how fast active power injection could be used as an uninterrupted power supply to the selected feeder, so that in case of under frequency load shedding the feeder will not experience a power outage. The results of analysis show that the selected feeder has uninterrupted power even though the grid was disconnected.